Efektivitas dan Keamanan Nifedipin dibandingkan dengan Labetalol pada Hipertensi dalam Kehamilan : Suatu Tinjauan Sistematik - Deby Dhevita Rahmania; Abdi Lathif Yukahadi (Universitas Muhammadiyah Manado, 2026)
Hypertensive disorders of pregnancy remain a leading cause of maternal and perinatal morbidity and mortality worldwide. Nifedipine and labetalol are commonly recommended as first-line antihypertensive agents during pregnancy; however, evidence regarding their comparative effectiveness and safety is still evolving. This systematic review aimed to evaluate and compare the effectiveness and safety of nifedipine versus labetalol in the management of gestational hypertension, chronic hypertension, and preeclampsia. The review was conducted according to PRISMA 2020 guidelines. A comprehensive literature search was performed in PubMed, ScienceDirect, and Google Scholar for randomized controlled trials published between 2016 and December 2025. Studies comparing nifedipine monotherapy with labetalol monotherapy and reporting systolic and/or diastolic blood pressure outcomes were included. Six RCTs involving 2,806 pregnant women met the inclusion criteria. Both drugs were effective in reducing blood pressure. Nifedipine demonstrated a faster onset of blood pressure reduction, particularly in acute hypertensive emergencies, with mean differences ranging from 12 to 17 minutes compared with labetalol. No significant differences were observed in long-term blood pressure control or neonatal outcomes. Maternal adverse effects were generally mild and comparable. Overall, both agents exhibit similar efficacy and safety profiles, with nifedipine offering advantages in rapid blood pressure control in acute settings.